Determinan Penghindaran Pajak: Peran Financial Distress, Capital Intensity, dan Pertumbuhan Penjualan - Loen, Mishelei; Praptiwi, Widia; Rahmah, Mulia; Rahmawantari, Dhistianti Mei (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2026)
This study aims to analyze the influence of financial distress, capital intensity, and sales growth on tax avoidance among property and real estate companies listed on the Indonesia Stock Exchange from 2021 to 2025. This study employs a quantitative method with an associative approach. The data used in this study are secondary data. The population consists of 92 companies, selected using purposive sampling. Data analysis in this study utilizes descriptive statistical techniques and linear regression analysis with the assistance of Statistical Package for the Social Sciences version 27. The findings indicate that financial distress and capital intensity influence tax avoidance, whereas sales growth does not influence tax avoidance. The implications of this study are expected to serve as a benchmark for making wiser decisions regarding tax avoidance while remaining within the boundaries of regulations established by the government.